2007
DOI: 10.1080/00103620701758873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Fertilizer, Foliar Fertilizer, and Growth Regulator Application on Milk Thistle Development, Seed Yield, and Silymarin Content

Abstract: An important consideration for milk thistle (Silybum marianum L.) cultivation is regulating development to lengthen the reproductive stage and increase seed yield with high silymarin content. The treatment of milk thistle with foliar fertilizers and growth regulators-thidiazuron (Dropp w ), 2,3,5-triiodobenzoic acid (Tiba w ), mepiquat chloride (Pix w ), and prohexadione-Ca (Regalis w )-resulted in an increase in the proportion of mature flower heads. Highest seed yield was observed in plants treated with Pix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
2
10
1
1
Order By: Relevance
“…Furthermore, mepiquat chloride did not affect seed yield and its components. In contrast, Geneva et al [20] observed that prohexadione-Ca and mepiquat chloride in combination with fertilization increased both the number of flower heads and seed yield in milk thistle crops.…”
Section: Seed Yield and Componentsmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, mepiquat chloride did not affect seed yield and its components. In contrast, Geneva et al [20] observed that prohexadione-Ca and mepiquat chloride in combination with fertilization increased both the number of flower heads and seed yield in milk thistle crops.…”
Section: Seed Yield and Componentsmentioning
confidence: 87%
“…These results may be attributed to the fact that despite the reduction in plant height with MC treatments, the number of flower heads, 1000-seed weight, and chlorophyll content were not affected. In contrast, Geneva et al [20] observed that the application of plant growth retardants, such as mepiquat chloride and prohexadione-Ca increased the silymarin yield in milk thistle, mainly due to an increase in seed production. Moreover, Stancheva et al [21] reported that thidiazuron combined with foliar fertilizer increased silymarin content by approximately 10%.…”
Section: Silymarin Content and Yieldmentioning
confidence: 90%
“…Like other plants, milk thistly acquires and assimilates nutrients in requisite quantities for better growth and yield (Geneva et al 2007;Školníková et al 2019). Some nutrients are both structurally and functionally important (e.g., nitrogen, phosphorous, calcium and sulfur), while others (e.g., K and Ca) are not part of plant structure but are required for physiological processes in soluble form (Taiz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of treatment milk thistle with foliar fertilizers and thidiazuron (Dropp Reg.) studied by (Geneva et al, 2008), and investigated that, The highest content of silymarin was found in plants treated with Dropp Reg.…”
Section: Thidiazuronmentioning
confidence: 99%